Correctional Intake Assessment and Case Planning: Application Development and Validation - Motiuk, Laurence L. (Criminal justice and behavior, 2021)
The Intake Assessment (IA) process in the Canadian federal correctional system results in an individualized treatment and supervision plan throughout the sentence. Two components, Static and Dynamic Factors Assessment, were examined to determine whether a streamlined version could be tailored for a hand-held mobile application and remain reliable and valid for correctional planning purposes. An Information Management System database was used to identify all first releases from federal custody over a 2-year period who had IA data available (N = 6,946). Analyses revealed statistically significant relationships and AUCs (area under receiver operating characteristic curves) for both the Static and Dynamic Factors components of IA with respect to reincarceration. Additional analyses revealed that the strongest predictors for returns to federal custody were criminal history as a youth or adult, substance misuse, and unemployment. A combined Static and Dynamic Factors score also yielded a simplified, robust, and incremental predictor of reincarceration for both men and women.